Criminal Acts of Bullying of Children in the Education unit - M. Yanto; Hasyim, Ali Fuad; khitam, Muhammad Chusnul; Fauziah, Putri Naillah (Jurnal Independent, 2026)
Cases of bullying that occur in educational units often involve children, both as perpetrators and victims. There are two factors that cause bullying cases to occur in the education unit. The first is external factors, which come from outside the individual which includes family, socioeconomic status, religion, culture, and gender. The second factor is internal in individuals including personality values, self-control, self-esteem, self-concept, and emotional intelligence, discrimination is mandatory to get access to quality education. The impact of bullying is on health, economic capacity, and social relationships. Child abuse is a complex problem and its solution is not easy. The formulation of the problems in this study is: How to be accountable for the crime of bullying against children in the education unit and how to regulate the crime of bullying against children in the education unit. The research method uses normative legal research with a legislative approach and a conceptual approach. The legal materials used include the Criminal Code, the Child Protection Law, the Juvenile Justice System Law, and the National Education System Law. From the results of the study, it can be concluded that: 1. Accountability for the crime of bullying of children under the age of 18 is only subject to actions such as return to parents or guardians or foster parents, treatment at LPKS, obligation to attend formal education and/or training held by private bodies, correction of criminal acts. 2. The regulation of the crime of child abuse is contained in Law Number 35 of 2014 concerning Child Protection and Law Number 11 of 2012 concerning the Child Criminal Justice System.